2001
DOI: 10.2165/00019053-200119090-00004
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Utility Analysis of Tissue Plasminogen Activator Therapy for Acute Ischaemic Stroke

Abstract: From the standpoint of cost effectiveness, treatment of acute ischaemic stroke with intravenous t-PA is an economically attractive strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
2
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 21 publications
2
69
2
1
Order By: Relevance
“…13,18 Within the 3-hour time window, studies have estimated a decrease in health expenditure by AUD $2669 during 1-year time-horizon 19 to AUD $3654 during a 30-year time-horizon. 26 Because tPA administration was also associated with health gain, it was considered a dominant strategy (less costly and more effective), and hence, ICERs were not calculated. These included 1 Australian study by Mihalopoulos et al, 19 but because this had been based on 1994 data, results may no longer be applicable.…”
Section: Discussionmentioning
confidence: 99%
“…13,18 Within the 3-hour time window, studies have estimated a decrease in health expenditure by AUD $2669 during 1-year time-horizon 19 to AUD $3654 during a 30-year time-horizon. 26 Because tPA administration was also associated with health gain, it was considered a dominant strategy (less costly and more effective), and hence, ICERs were not calculated. These included 1 Australian study by Mihalopoulos et al, 19 but because this had been based on 1994 data, results may no longer be applicable.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,15 Such studies have been the basis for many important cost-effectiveness analyses for stroke prevention and treatment modalities. [16][17][18] Childhood stroke cost data, however, are limited: there has been one published US cost analysis from a single children's hospital. 19 The costs of neonatal stroke have yet to be addressed.…”
mentioning
confidence: 99%
“…19 Also using NINDS data, Sinclair reported a savings estimate of $3800 CAD:1999 per tPA-treated patient over a lifetime (maximum 30 years). 20 These models produced absolute estimates based on trial data for patients treated <3 hours without considering relative service performance differences or the impact of prehospital identification. By applying pooled trial data for treatment up to 6 hours to a detailed model using an NHS perspective, Sandercock suggested that compared with standard care, there was a 78% probability of a gain in quality-adjusted survival during the first year with an incremental cost per additional QALY gained of £13 581 (GBP:price year not stated).…”
Section: Discussionmentioning
confidence: 99%